“They think we are all beggars”: The resilience of a person with disability in Ghana - Opoku, Maxwell Peprah; Gyamfi, Naomi; Badu, Eric; Mprah, Wisdom Kwadwo (Journal of Exceptional People, 2017)
In this study, the authors employed a single-participant approach to investigate the resilience of persons with disabilities in the face of discrimination and marginalisation. An interview was conducted with a woman living with physical disability in the capital of the Northern region of Ghana. The study found that despite barriers erected against a person with disabilities in the study area, the individual has striven to live independently by engaging in productive activities. The discussion of the study focused on the urgent need for society to empower persons with disabilities to enable them to utilise their inherent capabilities to allow them to become productive members of the society.
Keywords: Persons with Disabilities; postižení; Discrimination, Psychological; ženské pohlaví; zaměstnání pro postižené; Resilience, Psychological; vyprávění; psychická odolnost; diskriminace (psychologie); Humans; Female; Narration; lidé; Ghana; Employment, Supported